2013
DOI: 10.1016/j.ejmech.2013.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Development of potent dipeptide-type SARS-CoV 3CL protease inhibitors with novel P3 scaffolds: Design, synthesis, biological evaluation, and docking studies

Abstract: We report the design and synthesis of a series of dipeptide-type inhibitors with novel P3 scaffolds that display potent inhibitory activity against SARS-CoV 3CLpro. A docking study involving binding between the dipeptidic lead compound 4 and 3CLpro suggested the modification of a structurally flexible P3 N-(3-methoxyphenyl)glycine with various rigid P3 moieties in 4. The modifications led to the identification of several potent derivatives, including 5c-k and 5n with the inhibitory activities (Ki or IC50) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 26 publications
2
92
0
Order By: Relevance
“…Moreover, we showed that co-infection with a wild type virus rescued the replication of the replication-deficient SARS-CoV carrying a mutation in nsp4, suggesting that the membrane rearrangements inducing by the nsp3-nsp4 interaction are necessary to provide a site for the viral genome replication. Two cysteine proteases, nsp3 and nsp5 of SARS-CoV, participate in processing of the polyprotein to release other nsps, and chemical compounds that have been shown to suppress the proteinase activities (Konno et al, 2016;Ratia et al, 2008;Thanigaimalai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we showed that co-infection with a wild type virus rescued the replication of the replication-deficient SARS-CoV carrying a mutation in nsp4, suggesting that the membrane rearrangements inducing by the nsp3-nsp4 interaction are necessary to provide a site for the viral genome replication. Two cysteine proteases, nsp3 and nsp5 of SARS-CoV, participate in processing of the polyprotein to release other nsps, and chemical compounds that have been shown to suppress the proteinase activities (Konno et al, 2016;Ratia et al, 2008;Thanigaimalai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, compounds 9 and 10 displayed the best inhibitory potencies against 3CLpro ( K i values of 0.39 and 0.33 μM, respectively) . Further studies led to the identification of a rigid indole‐2‐carbonyl unit as one of the best P3 moieties, thus providing inhibitor 11 ( K i =0.065 μM) …”
Section: Cov Protease Inhibitorsmentioning
confidence: 98%
“…10 Unfortunately, to date, no protease inhibitors targeting SARS-CoV 3CL Mpro have been FDA-approved, despite significant research effort during the past fifteen years. [11][12][13][14][15][16][17] The 3CL M pro structure is composed of three domains. 18,19 Domains I (residues 8-101) and II (residues 102-184) are composed of antiparallel β-barrel structures and are the catalytic domains.…”
Section: Main Textmentioning
confidence: 99%